MIXED METHOD STUDY TENTANG IMPLEMENTASI MODEL ASUHAN KEBIDANAN “PARTNERSHIP CARE” DALAM PROSES PERSALINAN DI PRAKTIK MANDIRI BIDAN KOTA BANJARMASIN: Study Of Mixed-Method Application Of Midwife Care Model “Partnership Care” In Labor Process In Banjarmasin Midwife Practice - Rr. Sri Masdiputri (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Long parturition is the third largest contributor to maternal mortality in Indonesia, the incidence of prolonged labor in 2007 and 2012 remains the same at 5% (SDKI, 2012). The Partnership care model in childbirth is described by a situation where the midwife and woman become friends, friends, mutually support each other, have an equal position in the delivery process, thus partnership care can facilitate the delivery process and become the solution of choice in cases of prolonged labor.The results of a survey of 10 PMB midwives in Banjarmasin City found that 70% of PMBs did not implement the partnership care model of midwifery care in childbirth.This study aims to determine the implementation of the partnership care model of care in the delivery process by the Independent Practice of Midwives in the City of Banjarmasin quantitatively and qualitatively and to find inhibiting factors from the implementation of the partnership care model of care in the delivery process.The method used in this research is Mixed Method with sequential approach. The sample used is total sampling, namely all PMB in Banjarmasin City. Research results will be presented in quantitative and qualitative forms.